Mild infection induced by low-dose LPS does not impair follicular development and is beneficial to pregnancy in mice - Du, Yazhuo; Zeng, Yutian; Li, Shuo; Wang, Zhicheng; Su, Changqi; Zhang, Shilin; Ren, Yan; Song, Tianzeng; Zhang, Ming (Frontiers in Veterinary Science, 2023)
The reproductive tract is susceptible to infection by a variety of bacteria, which can impair ovarian and uterine function. However, there is little known about whether mild infection can harm follicle development and embryo implantation. Here we showed that the immune response to a mild infection simulated by low-dose LPS induced inflammatory factor IL-1b expression and decreased MMP2 expression involved in embryo implantation. LPS treatment also inhibited the ovulation process and reduced litter weight. Despite the immune response and the disturbed ovulation induced by treatment with low-dose LPS, the overall result was beneficial to mouse pregnancy. This research provides the necessary foundation for exploring the effects of mild bacterial infection on ovarian and uterine function in mammals.